Synaptic Vesicle Pools: An Update - Denker, Annette; Rizzoli, Silvio O. (Frontiers in Synaptic Neuroscience, 2010)
During the last few decades synaptic vesicles have been assigned to a variety of functional and morphological classes or “pools”. We have argued in the past (Rizzoli SO and Betz WJ, 2005, Synaptic vesicle pools, Nat. Rev. Neurosci. 6, 57-69) that synaptic activity in several preparations is accounted for by the function of three vesicle pools: the readily releasable pool (docked at active zones and ready to go upon stimulation), the recycling pool (scattered throughout the nerve terminals and recycling upon moderate stimulation), and finally the reserve pool (occupying most of the vesicle clusters and only recycling upon strong stimulation). We discuss here the advancements in the vesicle pool field which took place in the ensuing years, focusing on the behavior of different pools under both strong stimulation and physiological activity. Several new findings have enhanced the three-pool model, with, for example, the disparity between recycling and reserve vesicles being underlined by the observation that the former are mobile, while the latter are “fixed”. Finally, a number of altogether new concepts have also evolved such as the current controversy on the identity of the spontaneously recycling vesicle pool.